Carbon-use strategies in stem radial growth of two oak species, one Temperate deciduous and one Mediterranean evergreen: what can be inferred from seasonal variations in the δ13C of the current year ring?. (17th May 2019) - Vincent-Barbaroux, Cécile; Berveiller, Daniel; Lelarge-Trouverie, Caroline; Maia, Rodrigo; Máguas, Cristina; Pereira, João; Chaves, Manuela M; Damesin, Claire
Abstract: Tree ring synthesis is a key process in wood production; however, little is known of the origin and fate of the carbon involved. We used natural 13 C abundance to investigate the carbon-use process for the ring development in a temperate deciduous ( Quercus petraea (Matt.) Liebl.) and a Mediterranean evergreen ( Quercus ilex L.) oak. The sapwood carbon reserves, phloem sucrose contents, stem respired CO2 efflux and their respective carbon isotope compositions (δ 13 C) were recorded over 1 year, in the native area of each species. The seasonal δ 13 C variation of the current year ring was determined in the total ring throughout the seasons, as well as in slices from the fully mature ring after the growth season (intra-ring pattern). Although the budburst dates of the two oaks were similar, the growth of Quercus ilex began 50 days later. Both species exhibited growth cessation during the hot and dry summer but only Q. ilex resumed in the autumn. In the deciduous oak, xylem starch storage showed clear variations during the radial growth. The intra-ring δ 13 C variations of the two species exhibited similar ranges, but contrasting patterns, with an early increase for Q. petraea . Comparison between δ 13 C of starch and total ring suggested that Q. petraea (but not Q. ilex ) builds its rings using reserves during the first month of growth. Shifts in ring and soluble sugars δ 13 C suggested an interspecific difference in either the phloem unloading or the use of fresh assimilate inside the ring. A decrease in ring δ 13 C for both oaks between the end of the radial growth and the winter is attributed to a lignification of ring cell walls after stem increment. This study highlighted the differences in carbon-use during ring growth for evergreen and deciduous oaks, as well as the benefits of exploring the process using natural 13 C abundance.